A Gallium-doped cement for the treatment of bone cancers. The effect of ZnO ↔ Ga2O3 substitution of an ionomeric glass series on the rheological, mechanical, pH and ion-eluting properties of their corresponding glass polyalkenoate cements. (15th June 2021) - Phull, Sunjeev; Rahimnejad Yazdi, Alireza; Towler, Mark R
Abstract: The primary treatment for patients suffering from bone cancers is resection of the tumour followed by reconstruction of the damaged bone. Despite the administration of post-operative chemotherapy, tumour recurrence continues to present itself as a severe complication leading to re-operation. Attempts to incorporate chemotherapeutic drugs into bone cements elicits local toxic effects on healthy bone, which could compromise implant fixation. Alternatively, the local administration of gallium (Ga) may prove to be more effective. This report considers the development of a Ga ionomeric glass series (0.48SiO2 -0.355ZnO-0.06CaO-0.08SrO-0.02P2 O5 -0.005Ta2 O5, with 0.01–0.05 mol% substitution for ZnO). X-ray Diffraction (XRD) confirmed the amorphous glass structure and Energy Dispersive x-ray Fluorescence (EDXRF) verified the successful addition of Ga into the glass series at the expense of Zinc (Zn). A Ga-GPC series was then formulated by mixing the glass particles with aqueous poly(acrylic) acid (PAA) and trisodium citrate (TSC). Fourier transform infrared (FTIR) spectroscopy demonstrated no structural changes to the GPC matrix with the incorporation of Ga. Measurements of the rheological properties demonstrated an exponential increase in setting time with increasing Ga content. Furthermore, the addition of ≥ 3 mol% Ga demonstrated deleterious effects on the GPC's mechanical properties and an analysis of pH confirmed that it decreased with increasing Ga content, suggesting a reduction in glass reactivity and PAA cross-linking. Finally, inductively coupled plasma—optical emission spectrometry (ICP-OES) demonstrated the controlled release of Ga across the GPC series, which will prove beneficial to future in vitro studies.